Make a living through fish farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
The best option for producing more fish in Eastern Africa is fish farming. This leaflet explains how you can make a living from fish farming, focusing on rearing tilapia.